BEYOND BORDERS: THE LEGACY OF INDIAN MINIATURE PAINTINGS IN THE BRITISH MUSEUM - Bennabhaktula Lavanya, (PEOPLE: International Journal of Social Sciences, 2025)
"Beyond Borders: The Legacy of Indian Miniature Paintings in the British Museum" explores the journey of Indian miniature paintings from their origins in the courts of Indian rulers to their placement in one of the world's foremost museums. This paper examines the cultural, historical, and artistic value of these paintings, shedding light on their role in shaping global perceptions of Indian art. By analysing select pieces in the British Museum's collection, this study reflects on the legacy and continuing influence of Indian miniature art in contemporary museum practices. By exhibiting these paintings, the British Museum provides a platform for audiences to engage with Indian cultural history. This encourages a broader understanding of Indian traditions, religious iconography, and historical events, while highlighting the unique visual language of Indian miniatures.